The influence of the TaRL approach on the critical thinking ability of elementary school students in mathematics subject - Kusumaningrum, Farida; Fitrianawati, Meita; Taqiyuddin, Muhammad (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
The results of the PISA study revealed that students have low critical thinking skills in Indonesia, especially in mathematics. This study aims to evaluate the effect of the Teaching at the Right Level (TaRL) strategy on the critical thinking skills of fourth-grade elementary school students in solving arithmetic problems in Yogyakarta. This study used a quantitative approach with a nonequivalent control group experimental design. The instruments used included essay tests, observation sheets, and documentation. Data were analyzed through descriptive statistics and t-tests to test the hypothesis. The results of the analysis showed that the TaRL strategy significantly improved students' critical thinking skills in four main aspects. The t-test produced a significance value of 0.000 (<0.05), indicating a significant difference between the experimental and control groups. The average posttest score of the experimental group reached 81.5, which is higher than that of the control group, which obtained an average of 76. This increase is illustrated in students' abilities to identify problems, analyze information, evaluate solutions, and logically convey arguments. These findings indicate that the TaRL strategy is effective in improving learning outcomes and contributes to strengthening students' critical thinking skills from an early age. Thus, the implementation of TaRL can be an alternative adaptive and transformative learning strategy to improve the quality of basic education in Indonesia.